Analisis Pemerintah dalam Pembangunan Nasional dalam Konteks Infrastruktur di Kota Serang - Afrilian, Alita Harya; Saepudin, Eli Apud; Selfiana, Netti; Navyyaandhini, Adela Marviola; A'yun, Nova Qurrota; Puspita Sari, Della (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
infrastructure have a very strong relationship with social welfare and environmental quality as well as the process of economic growth of a region or area. Infrastructure development in Serang City has a very impactful role because it affects all sectors, but in the observations made there is still a lot of infrastructure that needs to be improved again because it can interfere with community activities, so it needs to be handled further by the local government so that it continues to always provide maximum service to the community and can improve the quality of infrastructure so that it can be used safely. In addition, it is still found in some areas that are still flooded if there is high intensity rainfall. because there are still many national development issues in the city of Serang, it is necessary to make very significant changes for the government to travel frequently in that direction, and it is hoped that the government can quickly deal with how to manage buildings because there are still many developments that are still unfinished in the process, This article aims to describe and analyze how national development in infrastructure in Serang City. Infrastructure greatly contributes to accelerating the condition of a region. if the infrastructure is adequate, it means that the condition of the area will be good and can improve the image of the city of Serang as the province of Banten.